2022
DOI: 10.3389/fcell.2022.816517
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Type I Interferon Responses to Influence Tumor-Immune Cross Talk in PDAC

Abstract: Immunotherapy has revolutionized the treatment of many cancer types. However, pancreatic ductal adenocarcinomas (PDACs) exhibit poor responses to immune checkpoint inhibitors with immunotherapy-based trials not generating convincing clinical activity. PDAC tumors often have low infiltration of tumor CD8+ T cells and a highly immunosuppressive microenvironment. These features classify PDAC as immunologically “cold.” However, the presence of tumor T cells is a favorable prognostic feature in PDAC. Intrinsic tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 236 publications
(258 reference statements)
0
5
0
Order By: Relevance
“…Effector CD8 + TNFRSF9 hi T cells were significantly enriched for TNF-α signaling via the NF-κB, EMT, and apoptosis pathways, whereas effector CD8 + TNFRSF9 lo T cells were enriched for pathways including IFN-γ response, oxidative phosphorylation, and IFN-α response relative to the TNFRSF9 hi cells ( Figure 7E ). These results suggested that increased TNFRSF9 expression in effector CD8 + T cells may lead to a shift in the inflammatory response program, where low expression of TNFRSF9 is associated with an IFN response that is important for cytotoxicity in Teffs ( Cattolico et al, 2022 ), to a TNF-responsive state associated with high expression of TNFRSF9 . Although TNF-α is involved in the CD8 + T cell antitumor activity ( Calzascia et al, 2007 ), it can also promote apoptosis of CD8 + T cells ( Zheng et al, 1995 ).…”
Section: Resultsmentioning
confidence: 98%
“…Effector CD8 + TNFRSF9 hi T cells were significantly enriched for TNF-α signaling via the NF-κB, EMT, and apoptosis pathways, whereas effector CD8 + TNFRSF9 lo T cells were enriched for pathways including IFN-γ response, oxidative phosphorylation, and IFN-α response relative to the TNFRSF9 hi cells ( Figure 7E ). These results suggested that increased TNFRSF9 expression in effector CD8 + T cells may lead to a shift in the inflammatory response program, where low expression of TNFRSF9 is associated with an IFN response that is important for cytotoxicity in Teffs ( Cattolico et al, 2022 ), to a TNF-responsive state associated with high expression of TNFRSF9 . Although TNF-α is involved in the CD8 + T cell antitumor activity ( Calzascia et al, 2007 ), it can also promote apoptosis of CD8 + T cells ( Zheng et al, 1995 ).…”
Section: Resultsmentioning
confidence: 98%
“…Cytotoxic or metabolic stress induced by chemotherapy and/or radiation can stimulate nucleic acid sensing pathways in both tumor cells and infiltrating immune cells to trigger type-I IFN signaling (INF-α and -β). 107 Type-I IFN is required for robust immune surveillance by directly or indirectly stimulating T-cells, natural killer (NK) cells, or macrophages in the TME. Chemotherapy in combination with immune checkpoint or myeloid inhibitors has shown promise in triggering antitumor immune responses in PDAC, however these responses have not produced durable outcomes.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%
“…Chemotherapy in combination with immune checkpoint or myeloid inhibitors has shown promise in triggering antitumor immune responses in PDAC, however these responses have not produced durable outcomes. 93 , 103 , 107 Tumor mutational status or changes in protein expression may underpin resistance to immunotherapy. Loss of the tumor suppressors STK11, CDKN2A, PTEN, and STING reduction in β2-microglobin are all associated with poor responses to chemotherapy and/or ICIs.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway, sensing cytoplasmic double-stranded DNA (dsDNA) of both foreign and self-origin, has been established as an essential mechanism implicated in the innate sensing [ 15 17 ]. Briefly, cGAS activated by the cytoplasmic dsDNA, catalyzes the synthesis of 2′-3′ cyclic GMP-AMP (cGAMP) and activates the adaptor protein STING, inducing the production of type I interferons (IFN-Is) and secretion of pro-inflammatory cytokine to trigger the innate immune response [ 18 ]. Growing evidence has indicated that IFN-Is play a key role in promoting the activation and maturation of dendritic cells (DCs), enhancing the antigen presentation for T cell priming, facilitating tumor immune infiltration, and in turn eliciting the anti-tumor immune responses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%